Emotional intelligence as an ability: a pilot study with dynamic stimuli - KRYMCHAK, Viktoriia; ROMANOVA, Yulia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The relevance of this study is determined by the need for valid, objective tools for measuring emotional intelligence as an ability that plays a key role in interpersonal interaction, psychological adaptation, and the development of emotional competence. This is particularly important in the fields of education, psychotherapy, professional selection and social rehabilitation. The aim of this study is to test the author's methodology for assessing emotional intelligence based on Mayer-Salovey's model of abilities using dynamic video stimuli. The object of the study is emotional intelligence as a cognitive ability. The subject of the study is the author's methodology for diagnosing emotional intelligence, which uses dynamic video stimuli.Methods. To achieve the set goal, general scientific methods (analysis, synthesis, systematisation) of theoretical literature on the problem of emotional intelligence and psychometrics were used. A theoretical analysis of modern approaches to measuring emotional intelligence, in particular models of abilities and traits, was carried out. The author's methodology was developed using dynamic video stimuli based on Mayer-Salovey's four-branch model. Descriptive statistics, calculation of internal consistency of scales (Cronbach's α coefficient), and correlation analysis were used to process the results of pilot testing in order to verify the relationships between the subscales of the methodology and individual criterion variables.Results. The study showed that the proposed methodology for measuring emotional intelligence as an ability has reasonable potential, but requires further refinement of individual tasks to improve their clarity and internal consistency. After making adjustments to the wording and structure of the test, a significant increase in the reliability of the instrument was recorded - the final Cronbach's alpha coefficient reached 0.86, which indicates a high level of internal consistency of the scales. The results confirm the possibility of further use and psychometric testing of the methodology on a larger sample.Conclusions. The results of the pilot study indicate that the developed methodology shows promise for the effective measurement of emotional intelligence as an ability, but its current application is limited by a number of important challenges and uncertainties. Further refinement and in-depth research will allow for a full assessment of the potential of this tool in psychodiagnostics. The results obtained provide a basis for future discoveries, but the final conclusions require comprehensive verification and confirmation.
Keywords: emotional intelligence; ability model; psychodiagnostics; pilot study; video stimuli; methodology development